Freedom of Speech for Twitter Users According to the Constitution - Amalia, Sukma Fitri; Wijayanti, Septi Nur (Jurnal Penegakan Hukum dan Keadilan, 2025)
Freedom of speech is the main pillar of a country with democratic principles. Advancements in science and technology have facilitated the utilization of freedom of expression in two-way communication on social media, particularly on Twitter. Twitter was chosen as a means of communication because it is easier to access and manage information and convey aspirations and ideas. This study aims to examine the constitutional provisions regarding freedom of speech for Twitter users and to identify the challenges related to its enforcement in Indonesia. This legal research employed normative legal research, utilizing the method of inventorying library materials and data processing techniques by selecting primary, secondary, tertiary, and non-legal data, which are systematically arranged to find more actual results. The results indicated that the regulation of freedom of opinion on Twitter needs to be studied further since the sanction setting was only found in Law Number 19 of 2016. The problems that arise in freedom of speech on Twitter include conveying hate speech and cyberbullying, and humiliation and harassment using vulgar words or verbal sexual harassment. There is a need to draft a special regulation on freedom of expression on Twitter, which is expected to become a pillar for regulating freedom of speech on electronic media so that there are no problems or restrictions on expressing opinions.